Audience Perception of Nollywood’s Role In Redefining Nigeria’s Identity Through Storytelling (Integral Research, 2025)
The remarkable rise of Nollywood, Nigeria's prolific film industry, has transformed it into a potent vehicle for reshaping the country's identity through storytelling. Existing scholarship has shown that Nollywood Known for its storytelling prowess, has transcended national boundaries, captivating audiences worldwide and offering narratives deeply rooted in the Nigerian experience that move beyond stereotypes. This paper seeks to address the central problem of understanding how Nollywood's narratives have influenced audience perceptions and redefined Nigeria's identity on a global scale. The Narrative Perception theory of Julian Hochberg was adopted as the theoretical framework. The study incorporates qualitative and quantitative methodology, using interviews, survey and descriptive analysis. Through these methods, the study examined how Nollywood's storytelling has evolved global perceptions of Nigeria. The study discusses the profound impact of Nollywood's storytelling on audience perception of its role in reshaping and redefining identity of Nigeria, emphasizing its potential to challenge stereotypes and rectify misconceptions. The study's findings underscore Nollywood's transformative role in redefining Nigeria's identity and shaping its global image through storytelling. Hence, the study offers recommendations for Nollywood stakeholders, policymakers, and scholars, emphasizing the importance of continued support for the industry and its potential to contribute to Nigeria's cultural diplomacy efforts and global influence.
Keywords: Audience Perception, Nollywood, Nigeria’s identity, Redefining Nigeria's identity, Storytelling, Global influence, Cultural policy, films.